2006
DOI: 10.1103/physrevd.73.109901
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Spontaneous excitation of an accelerated atom in a spacetime with a reflecting plane boundary [Phys. Rev. DPRVDAQ0556-282172, 064022 (2005)10.1103/PhysRevD.72.064022]

Abstract: We study a two-level atom in interaction with a real massless scalar quantum field in a spacetime with a reflecting boundary. The presence of the boundary modifies the quantum fluctuations of the scalar field, which in turn modifies the radiative properties of atoms. We calculate the rate of change of the mean atomic energy of the atom for both inertial motion and uniform acceleration.It is found that the modifications induced by the presence of a boundary make the spontaneous radiation rate of an excited iner… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 17 publications
1
52
0
Order By: Relevance
“…The DDC proposal successfully resolves the problem of the stability of an inertial atom in its ground state in vacuum as a result of the delicate balance between the contributions of vacuum fluctuations and radiation reaction to the rate of change of the mean atomic energy. Recent investigations using the DDC formalism on the excitation of uniformly accelerated two-level atoms in interaction with fluctuating quantized massless scalar fields in vacuum in a flat spacetime with [7] and without boundaries [8] and that of static atoms outside a Schwarzschild black hole [9] show that the delicate balance no longer exists in the cases under consideration, thus making the transition of the atom from ground state to excited states possible, i.e., excitation of atoms spontaneously occurs. The spontaneous excitation of uniformly accelerated atoms in the flat spacetime can be regarded as providing a physically appealing interpretation of the Unruh effect [10], since the spontaneous excitation of accelerated atoms gives a physically transparent illustration for why an accelerated detector clicks, while the spontaneous excitation of the static atoms outside a Schwarzschild black hole can be considered as providing another approach to the derivation of the Hawking radiation and it shows pleasing consistence of two different physical phenomena, the Hawking radiation and the spontaneous excitation of atoms, which are quite prominent in their own right.…”
Section: Introductionmentioning
confidence: 99%
“…The DDC proposal successfully resolves the problem of the stability of an inertial atom in its ground state in vacuum as a result of the delicate balance between the contributions of vacuum fluctuations and radiation reaction to the rate of change of the mean atomic energy. Recent investigations using the DDC formalism on the excitation of uniformly accelerated two-level atoms in interaction with fluctuating quantized massless scalar fields in vacuum in a flat spacetime with [7] and without boundaries [8] and that of static atoms outside a Schwarzschild black hole [9] show that the delicate balance no longer exists in the cases under consideration, thus making the transition of the atom from ground state to excited states possible, i.e., excitation of atoms spontaneously occurs. The spontaneous excitation of uniformly accelerated atoms in the flat spacetime can be regarded as providing a physically appealing interpretation of the Unruh effect [10], since the spontaneous excitation of accelerated atoms gives a physically transparent illustration for why an accelerated detector clicks, while the spontaneous excitation of the static atoms outside a Schwarzschild black hole can be considered as providing another approach to the derivation of the Hawking radiation and it shows pleasing consistence of two different physical phenomena, the Hawking radiation and the spontaneous excitation of atoms, which are quite prominent in their own right.…”
Section: Introductionmentioning
confidence: 99%
“…The controversy was resolved when Dalibard, Dupont-Roc and Cohen-Tannoudji(DDC) [5,6] proposed a formalism which distinctively separates the contributions of vacuum fluctuations and radiation reaction by demanding a symmetric operator ordering of atom and field variables. The DDC formalism has recently been generalized to study the spontaneous excitation of uniformly accelerated atoms in interaction with vacuum fluctuations of scalar and electromagnetic fields in a flat spacetime [7][8][9][10][11], and these studies show that when an atom is accelerated, the delicate balance between vacuum fluctuations and radiation reaction that ensures the ground state atom's stability in vacuum is altered, making possible the transitions to excited states for ground-state atoms even in vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…[7] when the vacuum fluctuations are further modified by the presence of boundaries. Recently the effects of modified vacuum fluctuations and radiation reaction due to the presence of a conducting plane boundary upon the spontaneous excitation of both an inertial and a uniformly accelerated atom interacting with a quantized real massless scalar field have been discussed [23]. It is found that the modifications induced by the presence of a boundary make the spontaneous radiation rate of an excited inertial atom to oscillate near the boundary and this oscillatory behavior may offer a possible opportunity for experimental tests for geometrical (boundary) effects in flat spacetime.…”
Section: Introductionmentioning
confidence: 99%